Mitochondria-Targeted Antioxidant Mito-Tempo Protects against Acetaminophen Hepatotoxicity - Du, Kuo (Arch Toxicol, 2016)
Acetaminophen (APAP) hepatotoxicity is characterized by an extensive mitochondrial oxidant stress. However, its importance as a drug target has not been clarified. To investigate this, fasted C57BL/6J mice were treated with 300 mg/kg APAP and the mitochondria-targeted antioxidant Mito-Tempo (MT) was given 1.5h later. APAP caused severe liver injury in mice, as indicated by the increase in plasma ALT activities and centrilobular necrosis. MT dose-dependently reduced the injury. Importantly, MT did not affect APAP protein adducts formation, glutathione depletion or c-jun N-terminal kinase activation and its mitochondrial translocation. In contrast, hepatic glutathione disulfide and peroxynitrite formation were dose-dependently reduced by MT, indicating its effective mitochondrial oxidant stress scavenging capacity. Consequently, mitochondrial translocation of Bax and release of mitochondrial intermembrane proteins such as apoptosis-inducing factor were prevented and nuclear DNA fragmentation was eliminated. To demonstrate the importance of mitochondria-specific antioxidant property of MT, we compared its efficacy with Tempo, which has the same pharmacological mode of action as MT but lacks the mitochondria targeting moiety. In contrast to the dramatic protection by MT, the same molar dose of Tempo did not significantly reduce APAP hepatotoxicity. In contrast, even a 3h post-treatment with MT reduced 70% of the injury, and the combination of MT with N-acetylcysteine (NAC) provided superior protection than NAC alone. We conclude that MT protects against APAP overdose in mice by attenuating the mitochondrial oxidant stress and preventing peroxynitrite formation and the subsequent mitochondrial dysfunction. MT is a promising therapeutic agent for APAP overdose patients.